Pendekatan Data Panel Metode Common Effect Terhadap Fluktuasi Harga Dinamis Jangka Panjang Ikan Pelagis Kecil (The Panel Data Approaches the Common Effects Method to Long-Term Dynamic Price Fluctuations of Small Pelagic Fish) - Rahim, Abd. (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2018)
The research conducted in South Sulawesi aims to estimate long-term dynamic price fluctuations of small pelagic fish. These objectives use multiple regression analysis method and classical assumption test (multicollinearity and autocorrelation) with Common Effect panel data method approach. Based on the time dimension using time series data from 1991-2014 originating from secondary data. The results of this study found that in general the dynamic long-term price equilibrium of small pelagic fish in South Sulawesi is positively influenced by the price of small pelagic fish itself, the price of small pelagic fish in the past, and the per capita income of the community. Therefore, it is necessary to support the local government or stockholders in order to increase the production of catches to minimize the price fluctuation in the form of increasing the Grosstonase (GT) sea fleet to reach the fishing ground in the further Exclusive Economic Zone (EEE), such as 6-12 miles. This has been referring to the government program since 2010 through the ministry of marine and fisheries, the blue revolution as a grand strategy in implementing the restructuring of the national fleet to increase the production of catches